2016
DOI: 10.1098/rsif.2016.0633
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tuning of mammalian sperm behaviour by hyperactivation, rheology and substrate adhesion: a numerical exploration

Abstract: The great mammalian sperm race encounters numerous microenvironments to which sperm must adapt and a fundamental sperm response is the change in its waveform owing to both fluid rheology and capacitation, with the latter associated with a hyperactivated beat pattern. Hence, in this modelling study, we examine the effect of different flagellar waveforms for sperm behaviour near adhesive substrates, which are representative of epithelia in female tract sperm reservoirs and the zona pellucida (ZP), which surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 53 publications
0
35
0
3
Order By: Relevance
“…Stable swimming is only possible when the Hamiltonian symmetry is broken (such as in the case where weak fluid viscoelasticity is included (Yazdi et al 2015)). Wall potential forces, included in numerical studies (Ishikawa & Pedley 2007;Spagnolie & Lauga 2012;Ishimoto & Gaffney 2016), give rise to an additional velocity perpendicular to the wall given by…”
Section: Discussionmentioning
confidence: 99%
“…Stable swimming is only possible when the Hamiltonian symmetry is broken (such as in the case where weak fluid viscoelasticity is included (Yazdi et al 2015)). Wall potential forces, included in numerical studies (Ishikawa & Pedley 2007;Spagnolie & Lauga 2012;Ishimoto & Gaffney 2016), give rise to an additional velocity perpendicular to the wall given by…”
Section: Discussionmentioning
confidence: 99%
“…In order to capture the effects of such surface forces, including the effects of contact with the boundary, we can include short-range repulsive boundary forces of steric origin, given per unit surface area and scaling in strength with the ratio of fluid viscosity and dimensional beating period, μ/T d . Following Ishimoto and Gaffney [45], we explicitly give the force per unit area in dimensional form as…”
Section: Repulsive Boundary Forcesmentioning
confidence: 99%
“…This is representative of the range of beat forms observed in experiments (Dresdner & Katz, 1981;Drobnis et al, 1988;Guerrero et al, 2011;Ooi et al, 2014;Suarez & Dai, 1992;Woolley & Vernon, 2001). Similar to previous models (Ishimoto & Gaffney, 2016;Omori & Ishikawa, 2016;Smith et al, 2009b), we assume that the two wave amplitudes are related via the chirality parameter α where B = αA for 0 ≤ α ≤ 1. Here, α = 0 corresponds to the planar case and α = 1 corresponds to the helical case.…”
Section: Calcium and Curvature Dynamicsmentioning
confidence: 99%
“…In these models, the flagellar beat form is an emergent property. Another approach is to prescribe the flagellar beat form (Curtis et al, 2012;Ishimoto & Gaffney, 2016;Ishimoto et al, 2017). In all of these modeling studies, regardless of how the flagellar beat form is modeled, the observed sperm trajectory is an emergent property of the coupled system accounting for the fluid dynamics and the swimmer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation